2017
DOI: 10.1002/bio.3317
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced chemiluminescence for trazodone trace analysis based on acidic permanganate oxidation in concurrent presence of rhodamine 6G

Abstract: A new sensitized chemiluminescence method by acidic permanganate oxidation was developed for the sensitive determination of trazodone. A fluorescent dye as used rhodamine 6G to increase a chemiluminescence intensity. Under optimum conditions, the liner range of the calibration curve was obtained for 1-5000 nmol/L. The limit of detection was calculated from 3σ of a blank was 0.23 nmol/L. The coexistent ions and substances had no interference with the chemiluminescence measurement. The chemiluminescence spectra … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Upon adding 2,4‐HD, RhB degradation was suppressed, which indicated that R–O• was also a contributor to RhB degradation (Figure 4e). CL emission was clearly affected by 2,4‐HD (Figure S9e), possibly because the intermediate formed by the oxidation of RhB by R–O• could promote CL in this system [37]. Mn 2+ has been reported to specifically eliminate CH 3 CO 3 • in PAA‐based AOPs [38].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon adding 2,4‐HD, RhB degradation was suppressed, which indicated that R–O• was also a contributor to RhB degradation (Figure 4e). CL emission was clearly affected by 2,4‐HD (Figure S9e), possibly because the intermediate formed by the oxidation of RhB by R–O• could promote CL in this system [37]. Mn 2+ has been reported to specifically eliminate CH 3 CO 3 • in PAA‐based AOPs [38].…”
Section: Resultsmentioning
confidence: 99%
“…NaN 3 was considered to be an effective scavenger of 1 O 2 [34]. In the presence of NaN 3 , the degradation efficiency and CL intensity sharply decreased along with an increase in NaN tem [37]. Mn 2+ has been reported to specifically eliminate CH 3 CO 3 • in PAA-based AOPs [38].…”
Section: Effect Of Experimental Parameters On Degradation and CL Emis...mentioning
confidence: 99%
“…The importance of this drug in the treatment of such disorders and the severity of associated adverse effects renders its reliable determination very important. Different determination methods have been reported, including spectrophotometry2,7 spectrofluorometry,2,8 chemiluminescence,9 voltammetry,1012 high-performance liquid chromatography (HPLC)- ultraviolet detection,13,14 HPLC-fluorescence1,15 and HPLC-mass spectroscopy (MS) 16. However, these techniques require expensive equipment, time-consuming methods and sometimes reproducibility and derivatization procedures.…”
Section: Introductionmentioning
confidence: 99%